Utility of a novel point-of-care test for albuminuria in communities at high risk for chronic kidney disease in Thailand - Aminu K Bello; Kriang Tungsanga; Nattachai Srisawat; Kearkiat Praditpornsilpa; Somkanya Tungsanga; Rungrawee Nantanawijit; Patcharakorn Kiatamornrak; Win Kulvichit; Umphan Ngoensawat; Sasipa Tachaboon; Janejira Dinhuzen; Watchadaporn Chaisuriyong; et al. (BMJ Public Health)
Introduction Chronic kidney disease (CKD) is a major public health concern, and early detection is crucial to prevent adverse outcomes. Albuminuria is an early marker and key prognostic marker in CKD, but reliable tools for its detection are limited particularly in low resource settings. We tested the utility of a novel, affordable point-of-care test (POCT) for albuminuria among high-risk individuals for CKD.Methods This is a community-based cross-sectional study covering 17 primary subdistrict healthcare units in Ban Phaeo District, Samut Sakhon Province, Thailand. The inclusion criteria were asymptomatic adult participants diagnosed with hypertension, diabetes and/or aged over 60 years. We measured serum creatinine and quantitative urine albumin–creatinine ratio (UACR) and administered POCT urine albumin strip test (Albii, K. BioSciences, Bangkok, Thailand) and urine dipstick test for protein. Participants with albuminuria or estimated glomerular filtration rate (eGFR) by CKD-EPI 2009 equation <60 mL/min/1.73 m2 were considered to have suspected CKD. We evaluated diagnostic performance of POCT urine albumin strip.Results Among 2307 participants, 489 (20.3%) participants had reduced eGFR and/or albuminuria. The median eGFR was 93.23 (87.82, 98.73) mL/min/m2, and the median UACR was 9.15 (5.09, 20.96) mg/g. The POCT urine albumin strip showed a sensitivity of 0.70, specificity of 0.97 and accuracy of 0.92 compared with the quantitative UACR. Conversely, the POCT urine dipstick for protein had poor sensitivity, positive predictive value and accuracy.Conclusion The urine albumin test strip is a highly effective tool to conduct point-of-care identification for early CKD among high-risk populations. Given the test’s diagnostic performance and ease of use, such test should be incorporated into health policy.